Self-perspective in episodic memory after parietal damage and in healthy ageing. (18th February 2019) - Russell, Charlotte; Davies, Sarah; Li, Korina; Musil, Anna-Sofia; Malhotra, Paresh A.; Williams, Adrian L.
Abstract: Although there is strong support from functional imaging studies for lateral parietal lobe involvement in episodic memory, patients with damage to these regions do not appear to suffer from severe deficits in this cognitive domain. As such there has been no definitive explanation of this area's precise involvement. Here, we hypothesised that parietal regions play a crucial role in episodic memory – specifically in recollecting details from an egocentric perspective. In order to test this hypothesis systematically, we designed a novel experimental task utilising a head-mounted camera to record images from the participant's perspective, enabling us to evaluate the integrity of memory from the individual's own point of view. In the first study we examined patients with parietal damage and in a second study, using fMRI, we examined young and older healthy participants. Right-hemisphere patients with parietal damage were able to recall information accurately when recollecting what items had been present and where these items had been. However, patients were significantly impaired when attempting to judge from which perspective they had viewed the scenes. Critically, the patient group showed no evidence of impairment on standard tests of episodic and working memory. Examination of healthy participants in the second study utilised multi-voxel pattern analysis on neural activity during the recognition phase of a similar task. This revealed sensitivity to be highest around the angular gyrus of the lateral parietal cortex for our critical comparison - that is, when viewing stimuli that were the same as their egocentric view during encoding versus the identical scene but presented from an alternative angle. Our results provide important evidence that parietal cortex is directly involved in egocentric spatial perspective aspects of episodic memory and demonstrate for the first time a specific deficit in episodic memory in patients with right parietal damage. Highlights: Damage to right parietal cortex leads to a specific deficit in episodic memory. This deficit is in recognition of the perspective from which a memory was encoded. MVPA in neuroimaging shows parietal involvement in recalling from own perspective. Supramarginal and angular gyri regions crucial for these aspects of episodic memory.